Place Names in Alabama - Foscue, Virginia O. (Book collections on Project MUSE., 1989)
Place Names in Alabama is the first systematic attempt to account for all the names of the counties, cities, town, water courses, bodies of water, and mountains that appear on readily available maps of Alabama. In dictionary format, this volume contains some 2,610 place names, selected according to strict criteria as outlined in the introductions, from more than 52,000 available for the state of Alabama. Included in each entry is a description of the geographical feature, its exact location, the etymology of each name the feature has carried through the yea.